Efficacy of Different Modalities and Frequencies of Physical Exercise on Glucose Control in People with Prediabetes (GLYCEX Randomised Trial) - Aina M Galmes-Panades; Miquel Bennasar-Veny; Paula Oliver; Natalia Garcia-Coll; Alice Chaplin; Sergio Fresneda; Laura Gallardo-Alfaro; Carmen García-Ruano; Jadwiga Konieczna; Alfonso Leiva; Lluis Masmiquel; Catalina Pico; et al. (Metabolites, 2022)
To assess the efficacy of different modalities and frequencies of physical exercise on glycaemic control in adults with prediabetes. A two-phase, parallel, randomised, controlled clinical trial will be carried out, in 210 participants. In phase 1, 120 participants will be randomized into four arms: (1) aerobic exercise, (2) aerobic exercise combined with resistance, (3) high-intensity intervallic exercise and (4) control group. In phase 2, 90 new participants will be randomized into three arms, using the exercise modality that showed the best glycaemic control in phase 1 in the following manner: (1) frequency of 5 days/week, (2) frequency of 3 days/week and (3) frequency of 2 days/week. The control group (n = 30) will be included in phase 1 to evaluate the effect of any type of intervention versus no intervention. Data collection will be performed at baseline and after 15 weeks of follow up. Sociodemographic data, medication, comorbidity, blood biochemical parameters, blood pressure, anthropometric measurements, body composition, physical activity, sedentary lifestyle, diet, smoking, alcohol consumption, quality of life and sleep questionnaires will be collected. Physical activity, sedentary behaviour and sleep will be further determined with an accelerometer, and continuous glycaemia will be determined with a glycaemic monitor, both during seven days, at two time points. The main dependent variable will be the reduction in the mean amplitude of glycaemic excursions. The impact of these interventions on health will also be evaluated through gene expression analysis in peripheral blood cells. The results of this study will contribute to a better understanding of the mechanisms behind the glucose response to physical exercise in a population with prediabetes as well as improve physical exercise prescriptions for diabetes prevention. Increasing glycaemic control in people with prediabetes through physical exercise offers an opportunity to prevent diabetes and reduce associated comorbidities and health costs.